Developmental Features of Lexical Richness in English Writings by Chinese Beginner Learners - Zhang, Huiping; Chen, Ming; Li, Xuelan (Frontiers in Psychology, 2021)
This paper reports a cross-sectional study that investigates the developmental features in second language writings by Chinese beginner learners of English by using four lexical richness measures—lexical sophistication, lexical variation, lexical density and lexical errors—from the perspective of the language exposure hypothesis. Specifically, the study compares English compositions written by Chinese students of grade 7, grade 8 and grade 9 in terms of lexical sophistication, lexical variation, lexical density and lexical errors. The English compositions were sampled from the Writing Corpus of Chinese Beginner Learners of English and the sample size of the three grades remained almost the same. The analysis revealed that lexical richness in the writing samples of beginner learners is comparatively low, with beginner learners transferring lexical features of the oral register to their second language writings; furthermore, all four measures yielded significant, albeit non-linear and unevenly paced, developments across grade levels. Based on the findings, several suggestions for vocabulary teaching are provided.